1986
DOI: 10.1002/vnl.730080103
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of PVC fusion (gelation)

Abstract: PVC fusion (gelation) occurs with melting of crystallites followed by recrystallization. This recrystallization, as it occurs at the primary particle boundary. physically ties together the structure into a three dimensional network. One way of measuring the extent of this three dimensional network structure is to measure the force required to deform the material through a zero land length capillary. We examine this test method for various molecular weight PVC compounds, with and without plasticizer, and for va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Although the degree of gelation G reaches a maximum around 200°C, as shown in Figure 5(a), the low-temperature endotherm ⌬Hm(A) continues to increase with the milling temperature, like the entrance pressure loss as shown in Figure 6(a). Terselius et al, 32 Krzewski and Collins, [33][34][35] Patel and Gilbert, 36 Summer and Rabinovitch, 20 and Obande and Gilbert 37 showed that with increasing the processing temperature and hence the gelation of rigid formulation suspension PVC, the entrance pressure loss in the capillary flow increases in an S-shaped fashion. In the present experimental results, although the degree of gelation G shows an S-shaped change [as shown in Fig.…”
Section: Melt Fracturementioning
confidence: 99%
See 2 more Smart Citations
“…Although the degree of gelation G reaches a maximum around 200°C, as shown in Figure 5(a), the low-temperature endotherm ⌬Hm(A) continues to increase with the milling temperature, like the entrance pressure loss as shown in Figure 6(a). Terselius et al, 32 Krzewski and Collins, [33][34][35] Patel and Gilbert, 36 Summer and Rabinovitch, 20 and Obande and Gilbert 37 showed that with increasing the processing temperature and hence the gelation of rigid formulation suspension PVC, the entrance pressure loss in the capillary flow increases in an S-shaped fashion. In the present experimental results, although the degree of gelation G shows an S-shaped change [as shown in Fig.…”
Section: Melt Fracturementioning
confidence: 99%
“…Entrance pressure loss is higher as DP and the milling temperature are higher 7,9,20 and the entrance pressure loss of extrudate milled at low extrusion temperatures below 180°C shows only a scarce dependency on DP at reextrusion at low temperatures below about 150°C. 20 The dependency of the entrance pressure loss on the DP of extrudate is weaker than that of the powder.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies1–16 have been reported so far on the effect of gelation (milling) on the flow processability (rheological properties) of PVC. Uryu et al1 studied the effect of milling on the viscosity of rigid‐formulation suspension PVC compounds and showed that the milling generally decreases the viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the PVC particles are broken to the size of PVC primary particles in the well-dispersed domains. The physical properties of the well-dispersed domains have been investigated by several methods, [4][5][6] but no information about the physical properties of the pseudonetwork domains has been reported, since it is difficult to measure the physical properties of the local domain. To design a highly functional polymer, it is desirable to investigate the mechanical properties of the local domains.…”
mentioning
confidence: 99%